Adsorption of hydrazine on XC3 (X = B, Al, N, Si, and Ge) nanosheets: A computational study. (1st March 2019) - Zheng, Fangfang; Dong, Huilong; Ji, Yujin; Li, Youyong
Abstract: Hydrazine (N2 H4 ) is promising as chemical hydrogen storage molecule, whose interaction with adsorption substrates is critical to its practical applications. Here, the adsorption configurations, adsorption performance and electronic properties of N2 H4 on XC3 (X = B, Al, N, Si, and Ge) nanosheets were systematically investigated by density functional theory (DFT) calculations. The computational results show that the most stable adsorption conformation of N2 H4 on XC3 nanosheets is associated with the element group of X. The adsorption of N2 H4 on NC3 nanosheet is physisorption, while on other four XC3 nanosheets are chemisorption, with the binding strength increasing as g _NC3 < a _GeC3 < a _SiC3 < c _BC3 < c _AlC3 ( g, a and c denote gauche, anti and cis conformations, respectively). The charge population and bond order analysis are performed to explain the adsorption performance and configuration selectivity of N2 H4 on XC3 nanosheets. The electronic properties of XC3 nanosheets before and after N2 H4 adsorption were compared through band structure and density of states analysis. Our investigations reveal that GeC3 nanosheet possesses the potential for N2 H4 sensing due to the band gap opening after N2 H4 adsorption as well as the stable performance against the different contents of N2 H4 . Highlights: N2 H4 chemisorbs on BC3, AlC3, SiC3, and GeC3 nanosheets but physisorbs on NC3 . N2 H4 exhibits conformation selectivity against X elements in XC3 nanosheets. Bond order analysis elucidates the adsorption performance of N2 H4 on XC3 . GeC3 is promising for N2 H4 sensing due to the band gap opening after adsorption.